A seed grows ebook - Portis, Antoinette (2022)
From a tiny seed to a huge, fold-out bloom, the transformative life cycle of a sunflower plays out in this bold read-aloud. A Sibert Honor Book! A Theodor Seuss Geisel Honor Book! To understand how a seed becomes a sunflower, you have to peek beneath the soil and wait patiently as winding roots grow, a stalk inches out of the earth, and new seeds emerge among blooming petals. " A seed falls, And settles into the ground, And the Sun shines, And the rain comes down, And the seed grows…" Leading up to a striking fold-out spread of a full-grown sunflower, the lively, bold illustrations in A Seed Grows offer a close-up view of each step of the growth cycle.  Additional material in the back of the book explains the science of plant life cycles, and goes into more detail on the ways in which flowers and seeds depend on other creatures. Antoinette Portis is the author of A New Green Day , a Publishers Weekly Best Book of the Year and NCTE Notable Book in Poetry, as well as the Sibert Honor winning Hey, Water! An American Library Association Notable Children's Book A CALIBA Golden Poppy Award Finalist A New York Public Library Best Book of the Year A Publishers Weekly Best Book of the Year A Junior Library Guild Gold Standard Selection A Horn Book Fanfare Title